(untitled) (Bulletin KNOB, 2001)
In the past Belgian (non-metamorphic) marble from the Maas region was widely applied and exported to far across the borders. It concerns black, red and grey variants originating from the Carboniferous and Devonian periods. Its transport was highly dependent on waterways. Consequently, the river Maas played an important part in the export to the north. The exploitation of black coal limestone, black marble, already took place in the early thirteenth century. In the fourteenth century the material was exported to Paris because of its purity and fine structure. Although local examples go back further in time, the trade and application of red marble did not really start until after 1500, and was especially used in the Southern Netherlands. Traders such as Nonon, Misson, Van Neurenberg and Cornelis Floris saw to a wider distribution and application of the material. The town hall of Antwerp and various memorial sculptures of the last named artist are examples of this. In spite of the large detour, the material was usually transported by way of Dordrecht. In the Northern Netherlands the application of coloured marble started later than that of black marble, which is notably found in early Renaissance sepulchral monuments. It was not until the seventeenth century that the types of marble referred to were widely applied, frequently in combination with Carrara marble, which in the north, from the early seventeenth century onwards, started to supersede English alabaster. The expensive material is to be found in an ecclesiastical context as well as in a government, public and court context. The traders and contractors responsible for its supply formed a close group of stone buyers, who were frequently related. Examples of this are the Van Neurenberg, Van Delft and De Keyser families. The marble traders did not concentrate exclusively on the trade in marble. It is known that the Van Neurenberg family made a lot of supplies of Namur stone and marl, but also of coal and lime. Their activities were aimed at luxury products, memorial sculptures and other church furniture, as well as wall cladding, quay walls, locks and sluices and pavements. By way of Amsterdam they and other traders supplied considerable consignments of marble for the East-Sea region and Scandinavia.